Programa “Aprender haciendo”, basado en el aprendizaje experiencial y su influencia en el desarrollo de la competencia resuelve problemas de cantidad -Trujillo, 2019 - Quenaya Rodriguez, Lesly Elizabeth (2021)
The objective of this research was to determine in what extent the "Aprender haciendo" program, based on the experiential learning, influences the level of development of competence and solves quantity problems in students of the 2nd grade of Primary Education of IE. 81007 “Modelo” - Trujillo, 2019. The type of research was applied and the design was quasi-experimental. The sample population was integrated by 26 girls in the experimental group and 27 girls in the control group. The "Aprender haciendo" program is based on the contributions of the author David Kolb in his experiential learning theory, which consisted of 16 workshops and a test was applied to evaluate the development of competence solving quantity problems. The results determined that the "Aprender haciendo" program, based on experiential learning, significantly influences on the level of development of competence and solves quantity problems in the second grade students of Primary Education of the aforementioned institution, since the greater part of the experimental group in the post-test were located in the outstanding achievement level with a percentage of 84.6% and because in the hypothesis of the Mann Whitney U it yielded a value of p = 4.0117E-9, being p <0.05, which implies that there is statistical significance.